2005
DOI: 10.1021/la047690v
|View full text |Cite
|
Sign up to set email alerts
|

Nonwetting Process for Achieving Surface Functionalization of Chemically Stable Poly(tetrafluoroethylene)

Abstract: Using a low-energy Ar+ ion-beam with and without a reactive gas, chemically stable poly(tetrafluoroethylene) (PTFE) films were modified to have special surface features. The adhesion strength between the PTFE and the copper was significantly improved because of both changes in the surface topography and chemical interactions due to PTFE functionalization (oxidation and amination). The surface modification altered the failure mode from adhesive failure for the unmodified PTFE/Cu interface to cohesive failure fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…In recent years, more and more research has been carried out on the functional modification of PTFE membranes using an irradiation technique [20,21]. A novel cation-exchange fiber, which was prepared by simultaneous irradiation and grafting of acrylic acid onto the surface of PTFE, has been successfully used to adsorb heavy metal ions [15,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more research has been carried out on the functional modification of PTFE membranes using an irradiation technique [20,21]. A novel cation-exchange fiber, which was prepared by simultaneous irradiation and grafting of acrylic acid onto the surface of PTFE, has been successfully used to adsorb heavy metal ions [15,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ion beam surface modification of biomaterials has been performed to improve surface biocompatibility (26)(27)(28)(29)(30)(31)(32)(33)(34)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). Our group has previously reported that ion beam surface modification of biomaterials can enhance biocompatibility (46)(47)(48)(49)(50) and change the chemical characteristic of the biomaterial surface (30); therefore, alteration and manipulation of the thrombogenicity (28,31) and control of the cell attachment properties (46,47) of a biomaterial surface are possible by ion implantation.…”
Section: Y Sugita Et Al 460mentioning
confidence: 99%
“…In the studies from other groups (51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63), ion beam surface modification has been performed on polymeric and metallic surfaces to enhance cell attachment and growth (51)(52)(53)(54)(55)(56), increase biocompatibility (52,55,57,58), prevent calcification (59), improve antibacterial activity (60,61), enhance adhesive strength between polymers and metals (62), create active binding sites for protein (63), and control surface wettability (53,58). We believe that we are the first to report that ion beam surface modification of a protein-coated biomaterial can simultaneously inhibit platelet adhesion and maintain the ability of endothelial attachment.…”
Section: Y Sugita Et Al 460mentioning
confidence: 99%
“…[17][18][19][20] In addition, PTFE can be easily functionalized by radiationinduced grafting. 21 In this research, we report on an efficient method for the selective immobilization of silver nanoparticles on a PTFE surface by using patterned graft polymerization based on ion irradiation.…”
Section: Introductionmentioning
confidence: 99%